The Impact of Macroeconomic Indicator on Islamic Insurance Demand in Indonesia - Salahuddin El Ayyubi; W Widyastutik; A. Anditta (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
This research aimed to determine the development of Islamic insurance industry in Indonesia and analyze the influence of macroeconomic indicators Islamic insurance demand in Indonesia. Ordinary Least Square (OLS) was used in this research with monthly time series data from January 2014 to December 2016. The results of this research indicated that the variables of money supply, interest rate, GDP per capita, and education had a positive (significant) effect to the Islamic insurance demand in Indonesia. Moreover, the inflation variable and dependency ratio had a negative (significant) effect to the Islamic insurance demand in Indonesia.